The reality of the organizational brilliance of physical Educators in the college of Physical Education and Sports Sciences / University of Baghdad from female students point of view - Hussein Kkmais Hussein (Eximia, 2024)
Achieving goals effectively reflects the success of the institution. However, unless this indicator is coupled with efficiency when achieving goals, the institution will be equal in its achievements, and distinction will remain unachieved. Perhaps the role of the teaching staff in pushing the institution or college towards brilliance focuses on their ability to motivate people on the one hand and their interest in achieving brilliance for the institution. On the other hand, the importance of the research lies in the institution’s reaching a prominent position through the brilliance and creativity of teaching and achieving competition between institutions that make it more brilliance. The study seeks to achieve the goal of the reality of brilliance and reveal the organizational style of teaching in the College of Physical Education and Sports Sciences / University of Baghdad through preparing a measure of organizational brilliance. For teachers.